2016
DOI: 10.1016/j.radonc.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Optimal adaptive IMRT strategy to spare the parotid glands in oropharyngeal cancer

Abstract: Early replannings proved the most beneficial for PG sparing, three replannings (weeks 1-2-5), representing an attractive combination for ART in oropharyngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
2
48
0
2
Order By: Relevance
“…For OAR, a significant difference was only seen between mean planned and delivered dose to the larynx (p = 0.007) and mandible (p = 0.001), although the median differences were small and presumably of no clinical consequence. Changes in dose to the mandible are more likely be due to rotational errors than to true anatomical changes [21,22]. For the other OAR, including the parotids, no difference in mean dose was found.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For OAR, a significant difference was only seen between mean planned and delivered dose to the larynx (p = 0.007) and mandible (p = 0.001), although the median differences were small and presumably of no clinical consequence. Changes in dose to the mandible are more likely be due to rotational errors than to true anatomical changes [21,22]. For the other OAR, including the parotids, no difference in mean dose was found.…”
Section: Discussionmentioning
confidence: 89%
“…1 also shows large incidental individual differences between planned and delivered dose to targets, which could very well justify ART. Meaningful use of ART improves quality of life and seems most effective early in treatment, as most anatomical changes occur then [5,6,22,24,25], which is especially true for centers where ART efforts are labor intensive and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The replanning strategies, timing, and optimal number of treatments remain unclear so far. Many researchers are investigating these issues, and some have made new progress 15, 37. We firmly believe that it will lead us to new important discoveries if these studies can be performed using CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in silico study by Castelli et al found a parotid gland mean dose decrease of 3.6 Gy compared to cumulative dose with six weekly replannings in 15 oropharyngeal cancer patients [24]. From the same group, a study by Zhang et al showed that 95% of this benefit could be achieved by three weekly replannings at the first, second and fifth week of treatment, however they still found a mean benefit of 2.2 Gy with a single adaptive replan [25]. One possible explanation for these differences could be a higher degree of patient selection in these studies, which focused on locally advanced oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%